Effect of saline water irrigations on physiological, biochemical and yield attributes of dual purpose pearl millet (Pennisetum glaucum) varieties - GOVIND MAKARANA; ASHWANI KUMAR; R K YADAV; RAKESH KUMAR; POOJA G SONI; CHARU LATA; PARVENDER SHEORAN (The Indian Journal of Agricultural Sciences, 2019)
A split-plot experiment with four replicates on performance of dual purpose pearl millet (Pennisetum glaucum L.) under different saline water irrigation was conducted during kharif 2015 at ICAR-CSSRI experimental farm, Nain, Panipat. The experiment was conducted with 4 main-plot treatment consisting of different levels of saline irrigation water [ Normal(~0.6 dS/m) and three levels of saline irrigation (ECiw 3, 6 and 9 dSm-1)] and two sub-plot treatments of varieties [ICMV-15111 and AVKB-19]. AVKB-19 variety was found robust and more stable than ICMV 15111 in terms of physiological attributes (relative water content, membrane injury and chlorophyll content) at all three periodic observations taken at 50 days after sowing (at 1st cut), 30 days and 60 days after 1st cut. Among biochemical attributes, total soluble sugars, proline, epicuticular wax content increased with increasing stress levels where as protein content decreased with increasing level of salinity stress. AVKB-19 variety accumulated significantly higher osmolyte content than ICMV-15111. Irrespective of salinity treatments, Na+ content (shoot and root) was recorded gradually high with ICMV-15111 than AVKB 19 at all study stages. AVKB 19 variety presented significantly higher shoot and root K+ content than ICMV 15111. Data on green fodder yield showed significant differences between two cultivars across different saline water levels. The AVKB-19 variety produced significantly higher mean green fodder yield (27.96 t/ha) as compared to ICMV-15111(25.51 t/ha). The AVKB-19 resulted into significantly maximum DM yield at the 1st as well as in 2nd cut (5.67 and 5.09 t/ha) over ICMV-15111. AVKB-19 variety produced significantly higher (16.26%) grain yield of 1.93 t/ha as compared to 1.66 t/ha in ICMV-15111. The magnitude of reduction (%) with increasing salinity over good quality irrigation water was observed 10.14, 20.74 and 37.33 with 3.0, 6.0 and 9.0 dS/m salinity water, respectively. Results concluded that AVKB-19 variety of pearl millet proved superior and may be adapted as a choice for getting higher grain as well as green fodder yield with better physiological and biochemical responses under saline environment.